2015
DOI: 10.1371/journal.pone.0127688
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Tracking to Understand Physical Activity and Sedentary Behaviour: Exploratory Study in UK Office Buildings

Abstract: Little is known of the patterns of physical activity, standing and sitting by office workers. However, insight into these behaviours is of growing interest, notably in regard to public health priorities to reduce non-communicable disease risk factors associated with high levels of sitting time and low levels of physical activity. With the advent and increasing availability of indoor tracking systems it is now becoming possible to build detailed pictures of the usage of indoor spaces. This paper reports initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…However, as these models also depend on the structure of the indoor environment, it remains to be investigated how they will work across different home environments. Another strategy to improve the location detection accuracy is to use multiple tags in each location placed in different positions and orientations, although this might come at the cost of decreased spatial resolution 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as these models also depend on the structure of the indoor environment, it remains to be investigated how they will work across different home environments. Another strategy to improve the location detection accuracy is to use multiple tags in each location placed in different positions and orientations, although this might come at the cost of decreased spatial resolution 16 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the RFID technology adopted in these studies required the tagged object to be within a few centimeters from the person standing, thereby limiting the utility for location detection. Some recent studies combined wearable activity monitors with RFID tags or Bluetooth beacons to measure the locations where physical activities and sedentary behaviors occur within indoor environments 16,17 . These systems have been applied to study the activity patterns of able-bodied and older adults in office spaces and care homes, respectively, but have not been yet validated within the iSCI population 18 …”
Section: Introductionmentioning
confidence: 99%
“…However, this technology is not accurate within buildings where the signal may be lost [ 8 ]. Other methods better suited to indoor measurements have been trialled, such as wireless location systems (e.g., radio frequency identification tags; RFID) [ 9 ] and wearable cameras [ 10 ]. However, authors of papers on both of these approaches have reported difficulties in obtaining usable data [ 9 , 11 ], with linking to activity data proving difficult with RFID tags and coding the large amounts of information generated from cameras remaining thus far difficult to automate.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is crucial to measure the time (the “when”), the place (the “where”), and the potential social settings where human movement behaviors (physical activity and sedentary time) occur. Recent methodological advances have emphasized the need for more holistic approaches, which can allow for greater specificity and flexibility in exploring and understanding the relationships between behavior and place [ 7 , 8 ]. Tracking and determining where specific movement behaviors are performed could provide valuable information and could greatly enhance research determining the correlates of physical activity and sedentary behaviors.…”
Section: Introductionmentioning
confidence: 99%